How detection of epigenetic alterations of blood-borne DNA could improve melanoma diagnosis. (July 2014) - Hatzimichael, Eleftheria; Syed, Nel; Lo Nigro, Cristiana; Rao, Bhavya; Crook, Tim
<x xml:space="preserve">Abstract</x> Detection in blood of the genetic and epigenetic changes present in metastatic cancers is opening up new possibilities in molecular diagnostics. A number of methodological and clinical issues await resolution before serum epigenetic biomarkers can be considered a routine part of the management of melanoma patients following primary excision. However, there is every possibility that blood testing for the presence of methylated DNA will become an integral part of the clinical follow-up of such patients. The ability to identify patients with subclinical (asymptomatic) metastatic melanoma, combined with new, highly active targeted and immunomodulatory agents, may lead to further improvements in outcomes for this patient population.